InDesign CS5 Bible. - Gruman, Galen (Bible., 2010)
Optimize the latest version of InDesign for your most efficient project workflow yet. InDesign is a powerful publishing tool that serves as the standard program for professional layout and design. The latest version boasts a variety of updates and enhancements. Packed with real-world examples and written by industry expert Galen Gruman, this in-depth resource clearly explains how InDesign CS5 allows for better typography and transparency features, speedier performance, and more user control than any other layout program.: Shows you the vast updates to the newest version of InDesign, including.